Developing novel hybrid reefs to provide both wave energy reduction and opportunities for ecological restoration - Benjamin K. Norris; Borja G. Reguero; Camila Gaido-Lasserre; David Gutierrez-Barcelo; Joseph Bartolai; Michael A. Yukish; Landolf Rhode-Barbarigos; Brian K. Haus; Taylor Squires; Gabriel Barajas Ojeda; Maria Maza; Javier L. Lara; et al. (Coastal Engineering, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

The benthic genus Prorocentrum (Dinophyceae) in Aotearoa New Zealand and Rangitāhua Kermadec Islands: Genetic diversity, distribution, and diarrhetic shellfish toxin profile - Tomohiro Nishimura; J. Sam Murray; Kirsty F. Smith; Lucy Thompson; Joshua Fitzgerald; Emillie Passfield; Muharrem Balci; D. Tim Harwood; Sarah Challenger; Masao Adachi; Lesley L. Rhodes (Harmful Algae, 2026)

Comparison of Pediatric and Adult Glucagon-Like Peptide-1 Receptor Agonist Exposures Reported To United States Poison Centers, 2017–2024 - Anjali Senthilkumar; Hannah L. Hays; Sandhya Kistamgari; Natalie I. Rine; Allison L. Rhodes; Christopher E. Gaw; Gary A. Smith (Journal of Medical Toxicology, 2026)
Introduction As glucagon-like peptide-1 receptor agonist (GLP-1) use has increased among children, a better understanding of the related adverse effects in this population is needed. Methods National Poison Data System data from 2017 to 2024 were analyzed to compare characteristics and trends of exposures involving GLP-1s reported to United States (US) poison centers (PCs) among children 6–17 years old with those of adults. Results There were 13,924 single-substance GLP-1 exposures reported to US PCs from 2017 to 2024. The rate of exposures per one million US population increased by 1,830.8% from 0.97 in 2017 to 18.79 in 2024, including a 4,805.0% increase among children 6–17 years old from 0.04 in 2017 to 1.97 in 2024, with the majority of the increase occurring after 2021. Most exposures (91.7%) were associated with no or mild effects, while moderate effects were observed in 8.0% and major effects occurred in 42 exposures; there were two deaths. Children 6–17 years old were more likely (RR: 2.66, 95% CI: 1.73–4.11) to be admitted than adults, and children 12–17 years old were more likely (RR: 1.68, 95% CI: 1.08–2.63) to experience a more serious medical outcome than adults. Children 6–17 years old with at least one clinical effect experienced vomiting (88.2%) more commonly than adults (61.3%) (RR: 1.44, 95% CI: 1.34–1.55). Additionally, exposures among children 6–17 years old were more likely to be attributable to intentional misuse (RR: 8.12, 95% CI: 6.47–10.17) than among adults. Conclusions This study provides national-level, real-world findings that may help inform clinical practice.

Effects of different soybean protein sources on growth performance, feed utilization efficiency, intestinal histology, and physiological gene expression of Pacific white shrimp (Litopenaeus vannamei) in green water and indoor biofloc system. - Khanh Q. Nguyen; Aya S. Hussain; Adela N. Araujo; Leila M. Strebel; Trenton L. Corby; Melanie A. Rhodes; Timothy J. Bruce; Jorge Cuéllar-Anjel; D. Allen Davis (Aquaculture, 2026)

The effects of pre-planting treatment strategies on understory vegetation in an urban forest patch - Samantha E. Fuentes-Gigliotti; Max R. Piana; Richard A. Hallett; Maximilian Blaustein; Dhan Parker; John L. Jensen; AeLin Compton; Luke Rhodes; Myla F.J. Aronson (Urban Forestry & Urban Greening, 2025)

Comparison and efficacy of soy-based ingredients in practical diets for Florida pompano (Trachinotus carolinus) - Trenton L. Corby; Trinh H. V. Ngo; Khanh Q. Nguyen; Adela Araujo; Leila Strebel; Stephanie Velasquez; Melanie Rhodes; Timothy J. Bruce; Marty Riche; D. Allen Davis (Aquaculture International, 2025)
Three Trials were performed to understand better how soy processed in different ways impacts the growth, feed conversion ratio, and health of the Florida pompano ( Trachinotus carolinus ). The first two growth Trials were performed to evaluate the efficacy of an open soy-based diet compared to a commercially produced, fish meal (FM)–based diet. Trial 1 compared a soy-based diet to a commercial FM-based diet using juvenile fish (23.2 ± 1.87 g) across six replicates over 42 days. The FM-based diet significantly outperformed the soy diet in final biomass ( p = 0.026), weight gain ( p = 0.006), and feed conversion ratio (FCR) ( p = 0.015). Trial 2 used larger fish (38.1 ± 0.86 g) with three replicates over 56 days and found no significant differences between diets. Histological samples of the distal intestine showed no statistical differences in symptoms conducive to soy-induced enteritis between the practical soy diet and the commercial FM diet. Trial 3 evaluated nine experimental soy-based diets in juvenile pompano (4.82 ± 0.09 g) across quadruplicate tanks for 76 days. The basal diet containing 49.97% solvent-extracted soybean meal (SBM) was compared with diets where SBM was replaced at 50% or 100% with low oligosaccharide SBM, soy protein concentrate, or enzyme-treated SBM, or at 25% or 50% with expeller-extruded SBM. No significant differences were found in weight ( p = 0.493), survival ( p = 0.925), or FCR ( p = 0.874). Histological analysis showed no adverse intestinal effects in lamina propria thickness, lamina propria cellularity, connective tissue thickening, or abundance of goblet cells.

The benthic and epiphytic marine dinoflagellates of Aotearoa New Zealand and Rangitāhua Kermadec Islands, an updated checklist from 2018 to 2024 - Lesley L. Rhodes; Tomohiro Nishimura; J. Sam Murray; Sarah C. Finch; Lucy Thompson; Kirsty F. Smith (New Zealand Journal of Marine and Freshwater Research, 2025)
A checklist collating records of New Zealand’s benthic and epiphytic dinoflagellate species was published on‐line in 2018 [Rhodes L, Smith KF. 2019. A checklist of the benthic and epiphytic marine dinoflagellates of New Zealand, including Rangitāhua/Kermadec Islands. N Z J Mar Freshw Res. 53:258–277. doi: 10.1080/00288330.2018.1492425 ]. Over the last six years, seventeen species from nine genera (three newly reported genera) have been documented, including sand‐dwelling species. Isolation and identification of species using traditional microscopic techniques combined with analysis of DNA sequencing data has been supplemented by high‐throughput sequencing techniques (i.e. metabarcoding). Toxin data, based on liquid chromatography mass spectrometry (LC‐MS/MS), and toxicity of isolates are included where applicable. Forty‐two benthic and epiphytic dinoflagellate genera, including genera having benthic life stages, have now been recorded in Aotearoa New Zealand coastal waters including Rangitāhua Kermadec Islands (new record genera in bold): Adenoides , Alexandrium , Amphidinium , Archaeperidinium , Azadinium , Biecheleria , Blastodinium , Bysmatrum , Cachonina , Coolia , Crypthecodinium , Cryptoperidiniopsis , Dinophysis , Durinskia , Ensiculifera , Fukuyoa , Fragilidium , Gambierdiscus , Gonyaulax , Gymnodinium , Gyrodinium , Heterocapsa , Karenia , Karlodinium , Kryptoperidinium , Lepidodinium , Ostreopsis , Pelagodinium , Pentapharsodinium , Pfiesteria , Polarella , Prorocentrum , Protodinium , Protoperidinium , Pseudadenoides , Pseudopfiesteria , Scrippsiella , Symbiodinium , Thecadinium , Togula , Vulcanodinium and Woloszynskia.

Effects of plant growth regulators on post-cryopreservation recovery and respiratory rate of Green Kangaroo Paw shoot tips - Xavier Rhodes; Lily M. Whelehan; Eliza Driffill; Eric Bunn; Ricardo L. Mancera; Bryn Funnekotter (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)
Plant growth regulators can have a significant impact on regeneration and regrowth of shoot tips after cryopreservation. This study investigated four cytokinins, two auxins and gibberellic acid at three different concentrations to assess their effect on the quality of regenerating shoot tips of the cryotolerant species Green Kangaroo Paw ( Anigozanthos viridis ) over a 400 h (approximately 2 weeks) recovery period. Shoot tip weight, length and respiratory rate were used as the key metrics for shoot tip performance throughout the recovery period. The control treatment with no plant growth regulator (PGRs) exhibited 58.1% regeneration, with a maximum regeneration of 79% observed with the 1 µM gibberellic acid treatment and minimum regeneration of 0% when 25 µM kinetin was applied. Higher concentrations of the PGRs used generally resulted in decreased regeneration and poor regrowth of the shoot tips. The use of zeatin and gibberellic acid at 1 µM in the recovery medium did not improve regeneration but did cause the shoots to grow significantly larger and longer, with a greater final respiration rate. The respiratory rate of regenerating and non-viable shoot tips remained very low until 120–168 h (5–7 d) post-cryopreservation, after which the regenerating shoot tips started to show significant increases in respiratory rate compared to the non-viable shoot tips. These findings suggest that the role of PGRs on increasing oxygen consumption is mostly due to their effects on promoting cell proliferation and tissue growth.

Assessing new microalgae species as potential feed for bivalve spat in nursery culture - Leslie T. Sampollo; Lesley L. Rhodes; María Múgica; Andrew G. Jeffs (New Zealand Journal of Marine and Freshwater Research, 2025)
Microalgae remains a primary food source for hatchery and nursery culture of juvenile bivalves. However, there is a mismatch between the characteristics of the microalgae currently used in nursery culture and the feeding abilities and nutritional requirements of juveniles of some bivalve species, such as the green‐lipped mussel, Perna canaliculus . Therefore, there is a need to identify new species of microalgae for this purpose that have favourable cell size, good growth performance under culture conditions and appropriate nutritional content for juvenile bivalves by using these characteristics as primary selection criteria. In this study, the growth performance under standard culture conditions of four microalgae species ( Chrysochromulina camella , Gymnodinium simplex , Pyramimonas parkeae and Stephanodiscus niagarae ) which are of a sufficiently large cell size to meet the needs of juvenile mussels (i.e. 10–20 µm size range) were tested in comparison to three commonly cultured commercial species ( Chaetoceros muelleri , Diacronema lutheri and Tisochrysis lutea ). Results show that G. simplex , S. niagarae and the two strains of P. parkeae ( P. parkeae (C) and P. parkeae (I)) can achieve similar biomass as the reference species in the intermediate (1 L) culture stages despite the large difference in cell densities. The poor growth of C. camella in F/2 media indicates a necessity of determining its appropriate culture conditions before further assessing its suitability as a nursery feed for juvenile bivalves. The proximate analysis of S. niagarae , G. simplex and P. parkeae (I) reveals nutritional profiles conducive to spat development. However, the P. parkeae (C) strain contained low carbohydrate content, suggesting inferior nutritional value compared to the P. parkeae (I) strain, showing that variants of the same species can have different biochemical composition and suggesting the former might have limited suitability for feeding in nursery culture. The findings indicate that G. simplex , S. niagarae and P. parkeae (C) hold sufficient promise as spat feed in nursery culture to warrant further testing to confirm their efficacy as live microalgal feed for bivalve spat.

Designing modular, artificial reefs for both coastal defense and coral restoration - Benjamin K. Norris; Borja G. Reguero; Joseph Bartolai; Michael A. Yukish; Landolf Rhode-Barbarigos; Brian K. Haus; Gabriel Barajas Ojeda; Maria Maza; Javier L. Lara; Michael W. Beck (Coastal Engineering, 2025)

Caught in headlights: Captive white-tailed deer responses to variations in vehicle lighting during imminent collision scenarios - Carson J. Pakula; Gino J. D'Angelo; Adrianna Mowrer; Olin E. Rhodes; Travis L. DeVault (Applied Animal Behaviour Science, 2025)

Landholders’ intentions to engage in private land conservation agreements under climate risk - Nanda Kaji Budhathoki; Kelly S. Fielding; Jonathan R. Rhodes; Carla L. Archibald; Daniel Lunney; James Brazil-Boast; Scott Benitez Hetherington; James A. Fitzsimons; Md Sayed Iftekhar (Journal of Environmental Management, 2025)

Analog modeling of landslide dynamics: Case study from the Andean Mesón Alto deposit, Central Chile (∼33°40′S) - L. Pinto; S.A. Sepúlveda; C. Lefeuvre; C. Albornoz; J. Rhodes; P. Jara; P. Muñoz; K. Deckart (Geomorphology, 2025)

Uptake of metals, metalloids, and radiocesium varies with habitat use among passerine communities at coal combustion and nuclear fission legacy waste sites - Courtney S. Werner; Mary Chapman; Olin E. Rhodes; Travis L. DeVault (Environmental Pollution, 2025)

Effects of minimum dissolved oxygen setpoints for aeration in semi-intensive pond production of Pacific white shrimp (Litopenaeus vannamei) - Adela N. Araujo; Christian F. San Andres; Khanh Q. Nguyen; Trenton L. Corby; Melanie A. Rhodes; Julio García; Luke A. Roy; D. Allen Davis (Aquaculture, 2025)

Toward understanding the hydrologic, ecologic and community flooding implications of coastal restoration strategies: Sediment diversions - Ahmed M. Khalifa; Ehab A. Meselhe; Kelin Hu; Denise Reed; Rachel Rhode; Natalie L. Snider (Estuarine, Coastal and Shelf Science, 2024)

Influence of habitat and baiting strategy on oral rabies vaccine bait uptake by raccoons in the southeastern United States - Jacob E. Hill; Madison L. Miller; Richard B. Chipman; Amy T. Gilbert; James C. Beasley; Guha Dharmarajan; Olin E. Rhodes (Applied Animal Behaviour Science, 2024)

Trace metal transfer to passerines inhabiting wastewater treatment wetlands - Courtney S. Werner; Mary Chapman; Jonathon Skaggs; Olin E. Rhodes; Travis L. DeVault (Science of The Total Environment, 2024)

Glucagon-Like Peptide-1 Receptor Agonist Cases Reported to United States Poison Centers, 2017–2022 - Christopher E. Gaw; Hannah L. Hays; Cydney A. Kemp; Sandhya Kistamgari; Henry A. Spiller; Natalie I. Rine; Allison L. Rhodes; Motao Zhu; Gary A. Smith (Journal of Medical Toxicology, 2024)
Introduction Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are a class of medications for management of diabetes and obesity. The objective of this study is to characterize the epidemiology of GLP-1RA cases reported to US poison centers. Methods We analyzed cases involving a GLP-1RA reported to the National Poison Data System during 2017–2022. Results There were 5,713 single-substance exposure cases reported to US poison centers involving a GLP-1RA. Most cases were among females (71.3%) and attributable to therapeutic errors (79.9%). More than one-fifth (22.4%) of cases were evaluated in a healthcare facility, including 0.9% admitted to a critical care unit and 4.1% admitted to a non-critical care unit. Serious medical outcomes were described in 6.2% of cases, including one fatality. The rate of cases per one million US population increased from 1.16 in 2017 to 3.49 in 2021, followed by a rapid increase of 80.9% to 6.32 in 2022. Trends for rates of serious medical outcomes and admissions to a healthcare facility showed similar patterns with 129.9% and 95.8% increases, respectively, from 2021 to 2022. Conclusions Most GLP-1RA cases reported to US poison centers were associated with no or minimal effects and did not require referral for medical treatment; however, a notable minority of individuals experienced a serious medical outcome or healthcare facility admission. The rate of reported cases increased during the study period, including an 80.9% increase from 2021 to 2022. Opportunities exist to improve provider and patient awareness of the adverse effects of these medications.

Correction: Population genetics of the endangered Clanwilliam sandfish Labeo seeberi: considerations for conservation management - Clint Rhode; Shaun F. Lesch; Kelvin L. Hull; Ruhan Slabbert; Martine S. Jordaan (Aquatic Sciences, 2024)

Fatty acid production and associated gene pathways are altered by increased salinity and dimethyl sulfoxide treatments during cryopreservation of Symbiodinium pilosum (Symbiodiniaceae) - Joseph K. Kihika; John K. Pearman; Susanna A. Wood; Lesley L. Rhodes; Kirsty F. Smith; Matthew R. Miller; Juliette Butler; Ken G. Ryan (Cryobiology, 2024)

Population genetics of the endangered Clanwilliam sandfish Labeo seeberi: considerations for conservation management - Clint Rhode; Shaun F. Lesch; Kelvin L. Hull; Ruhan Slabbert; Martine S. Jordaan (Aquatic Sciences, 2024)
The Cape Fold Ecoregion (CFE) is one of southern Africa’s unique aquatic ecoregions and its freshwater fish fauna is characterized by high levels of endemism. As with many other Mediterranean-type ecosystems, the region is also a hotspot for threatened and range-restricted freshwater fish. Many of the CFE’s endemic species are at risk for extinction, with declines in population sizes and distribution ranges. The Clanwilliam sandfish Labeo seeberi is an example of such a species and is considered one of South Africa’s most endangered large migratory cyprinids. This species is endemic to the Olifants/Doring river system in the CFE and has been subject to a major population decline, mainly as a result of invasive alien fish and adverse climate events. Little is known of the genetics of the Clanwilliam sandfish, thus this study aimed to provide basic population genetic parameters to inform future conservation interventions. Both microsatellite and mitochondrial DNA (mtDNA) markers were used to assess populations from three sites within the Olifants/Doring river system. Genetic diversity was moderate to low and did not reflect the drastic decline expected on the basis of previous relative abundance data. This is likely due to a lag effect between ecological/life history demographics (due to juvenile recruitment failures) and population genetic composition. Furthermore, there was limited genetic differentiation between the sampling locations, suggesting a single breeding population, but mtDNA haplotype distribution and slight divergence of the smaller populations does suggest that the population might have become recently fragmented. The results show that the effective population size of the current breeding population might still be sufficient to maintain evolutionary potential in the short term, which could act as a buffer until conservation strategies focusing on protecting breeding animals and maximizing juvenile survival can restore population numbers.

Bioaccumulation of contaminants in Scarabaeidae and Silphidae beetles at sites polluted by coal combustion residuals and radiocesium - Ansley E. Silva; Robert J. Speakman; Brittany F. Barnes; David R. Coyle; James C. Leaphart; Erin F. Abernethy; Kelsey L. Turner; Olin E. Rhodes; James C. Beasley; Kamal J.K. Gandhi (Science of The Total Environment, 2023)

Diversity and distribution of benthic dinoflagellates in Tonga include the potentially harmful genera Gambierdiscus and Fukuyoa - Phoebe A. Argyle; Lesley L. Rhodes; Kirsty F. Smith; D.Tim Harwood; Tuikolongahau Halafihi; Islay D. Marsden (Harmful Algae, 2023)

Sub-tropical benthic/epiphytic dinoflagellates of Aotearoa New Zealand and Rangitāhua Kermadec Islands - Lesley L. Rhodes; Kirsty F. Smith; J. Sam Murray; Emillie M F Passfield; Roberta D'Archino; Wendy Nelson; Tomohiro Nishimura; Lucy Thompson; Tom Trnski (Harmful Algae, 2023)

Assessing efficiency of fine-mapping obesity-associated variants through leveraging ancestry architecture and functional annotation using PAGE and UKBB cohorts - Mohammad Yaser Anwar; Mariaelisa Graff; Heather M. Highland; Roelof Smit; Zhe Wang; Victoria L. Buchanan; Kristin L. Young; Eimear E. Kenny; Lindsay Fernandez-Rhodes; Simin Liu; Themistocles Assimes; David O. Garcia; et al. (Human Genetics, 2023)

Driving in the dark: Deciphering nighttime driver detection of free-ranging roadside wildlife - Carson J. Pakula; Shane Guenin; Jonathon Skaggs; Olin E. Rhodes Jr.; Travis L. DeVault (Transportation Research Part D: Transport and Environment, 2023)

Long-read Sequencing and de novo Genome Assembly of Three Aspergillus fumigatus Genomes - Samuel J. Hemmings; Johanna L. Rhodes; Matthew C. Fisher (Mycopathologia, 2023)
Aspergillus fumigatus is a genetically diverse fungal species, which is near ubiquitous in its global distribution and is the major cause of the life-threatening disease invasive aspergillosis. We present 3 de novo genome assemblies that were selected to be representative of the genetic diversity of clinical and environmental A. fumigatus . Sequencing using long-read Oxford Nanopore and subsequent assembly of the genomes yielded 10–23 contigs with an N50 of 4.05 Mbp to 4.93 Mbp.

Beyond ecology: ecosystem restoration as a process for social-ecological transformation - Anazélia M. Tedesco; Sofía López-Cubillos; Robin Chazdon; Jonathan R. Rhodes; Carla L. Archibald; Katharina-Victoria Pérez-Hämmerle; Pedro H.S. Brancalion; Kerrie A. Wilson; Mariana Oliveira; Diego F. Correa; Liz Ota; Tiffany H. Morrison; et al. (Trends in Ecology & Evolution, 2023)

Exploring the role of boundary work in a social-ecological synthesis initiative - Barbara Schröter; Claudia Sattler; Jean Paul Metzger; Jonathan R. Rhodes; Marie-Josée Fortin; Camila Hohlenwerger; L. Román Carrasco; Örjan Bodin (Journal of Environmental Studies and Sciences, 2023)
Inter- and transdisciplinary collaboration in environmental studies faces the challenge of communicating across disciplines to reach a common understanding of scientific problems and solutions in a changing world. One way to address current pressing environmental challenges is to employ a boundary work approach that uses activities across borders of separated field of research. But how can this look like in practice? In this research brief, we self-evaluated the boundary work approach in a synthesis group on socio-ecological systems, based on an online survey with participants. Here, we discuss how boundary work can be used to integrate the knowledge from natural and social scientists both working on social-ecological systems. We found participants were selected to be acted as boundary spanners and were willing to cooperate for solving multidisciplinary issues regarding the understanding, management, and maintenance of ecosystem services. A social-ecological network analysis framework served as a boundary concept and object for communication and knowledge integration. Being familiar with a joint boundary concept like ecosystem services prior to the working group event supported the communication of participants. These results indicate that synthesis initiatives could strategically leverage boundary work through the careful selection of members, with the inclusion of boundary spanners, as well as prior joint identification of boundary concepts and objects.

Scavenging dynamics on Guam and implications for invasive species management - Jacob E. Hill; Kelsey L. Turner; Joshua B. Smith; Matthew T. Hamilton; Travis L. DeVault; William C. Pitt; James C. Beasley; Olin E. Rhodes (Biological Invasions, 2023)

Assessing siliceous sinter matrices for long-term preservation of lipid biomarkers in opaline sinter deposits analogous to Mars in El Tatio (Chile) - Laura Sánchez-García; María Ángeles Lezcano; Daniel Carrizo; Rita Severino; Miriam García-Villadangos; Sherry L. Cady; Kim Warren-Rhodes; Nathalie A. Cabrol; Víctor Parro (Science of The Total Environment, 2023)

Inflammatory profiles, gut microbiome, and kidney function are impacted after high-fidelity firefighter training - Madelyn C. Houser; Daniel J. Smith; David Rhodes; Judith L. Glick-Smith; Phillip Chovan; Erin Ferranti; Sandra B. Dunbar; Malú G. Tansey; Vicki Hertzberg; Valerie V. Mac (International Journal of Hygiene and Environmental Health, 2023)

Evaluation of the Reveal® rapid AST system to assess the susceptibility of Pseudomonas aeruginosa from blood cultures - J. Couchot; D. Fournier; M. Bour; L. Rajeev; P. Rhodes; P. Singh; K. Jeannot; P. Plésiat (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Molecular detection and distribution of the genera Amphidoma and Azadinium (Amphidomataceae, Dinophyceae) in the coastal waters of Aotearoa/New Zealand - Muharrem Balci; Lesley L. Rhodes; Tomohiro Nishimura; J. Sam Murray; D. Tim Harwood; A. Lincoln MacKenzie; Tony Bui; Catherine Moisan; Lucy Thompson; Kirsty F. Smith (New Zealand Journal of Marine and Freshwater Research, 2023)
Molecular‐based approaches for harmful algal bloom species, which can be difficult to identify by light microscopy, are important tools for detecting and predicting the blooms. In this study, 84 samples from Aotearoa/New Zealand coastal waters that contained Azadinium ‐like cells were analysed using an Amphidomataceae real‐time PCR assay. Nineteen samples were positive, and 24 Azadinium ‐like clonal isolates were established from these samples. Subsequently, only five isolates from one sampling point were positive using the real‐time PCR assay. Four of the five isolates were genetically identified as Amphidoma languida and one as Azadinium dalianense . The field samples were analysed retrospectively using the species‐specific real‐time PCR assays; Am. languida was detected from the temperate areas, while Az. poporum and Az. spinosum were detected at one site. Two representative strains of each species were analysed by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS), including Am. languida, which is known as toxic in the previous studies, but neither produced the currently monitored azaspiracids (AZAs). These two newly recorded species for New Zealand are important findings. The results highlight the need for more information on the spatio‐temporal variations of potentially toxic Amphidomataceae species and the risk of AZAs in New Zealand coastal waters.

Development of an enzyme-linked immunosorbent assay for the diagnosis of feline tuberculosis - Jordan L. Mitchell; Chris Wilson; Janet E. Alexander; Shelley G. Rhodes; Danièlle A. Gunn-Moore; Jayne C. Hope (Veterinary Immunology and Immunopathology, 2023)

Phenotypic Variants of Azole-Resistant Aspergillus Fumigatus that Co-exist in Human Respiratory Samples are Genetically Highly Related - Alireza Abdolrasouli; Johanna L. Rhodes (Mycopathologia, 2022)
Respiratory specimens obtained from patients with chronic forms of aspergillosis contain phenotypic variants of azole-resistant Aspergillus fumigatus (ARAF) that co-exist in the airway. Here we aimed to study whether phenotypic variants of ARAF that co-exist in clinical specimens were genetically distinct. A panel of six phenotypic variants of ARAF cultured from two sputum samples collected from two patients with chronic aspergillosis were included. Preliminary identification of all isolates was obtained using MALDI–ToF mass spectrometry and confirmed by AsperGenius ® real-time PCR assay. Antifungal susceptibility testing was determined using EUCAST E.Def 9.3 microbroth dilution. Genomic DNA libraries were constructed with the Illumina TruSeq Nano kit. Prepared whole-genome libraries were sequenced on an Illumina HiSeq 2500. Whole genome data were converted into presence/absence of a SNP with respect to the Af293 reference genome. Colonies of ARAF that co-existed in one respiratory sample demonstrated marked phenotypic diversity. Two cyp51A polymorphisms were found among azole-resistant isolates: TR 34 /L98H/T289A/I364V/G448S was consistently present in four variants with a pan-azole resistant phenotype and TR 34 /L98H was detected in two variants (itraconazole MIC > 16 mg/L). WGS typing showed that despite marked phenotypic variation, each sample contained a population of highly genetically related azole-resistant A. fumigatus variants. Our SNP analysis suggest that mechanisms additional to genetic-based variation are responsible for phenotypic diversity. Our data demonstrate that the phenotypic variants of ARAF that co-exist in clinical specimens are highly clonal and strongly suggest their origination from a single common ancestor.

Risk factor determination and qualitative risk assessment of Mucormycosis in Harbor Porpoise, an emergent fungal disease in Salish Sea marine mammals - Stephanie A. Norman; Jessica L. Huggins; Dyanna M. Lambourn; Linda D. Rhodes; Michael M. Garner; Jennie L. Bolton; Joseph K. Gaydos; Alyssa Scott; Stephen Raverty; John Calambokidis (Frontiers in Marine Science, 2022)
Mucorales infections are increasing in frequency and are a One Health pathogen of concern. In humans and domestic animals, risk factors include being immunocompromised, elevated circulating serum iron, contaminated open wounds, or metabolic diseases such as ketoacidosis or uncontrolled diabetes. Mucormycosis was first identified in 2012 in Pacific Northwest marine mammals, predominantly in harbor porpoises. We performed an assessment to determine the overall qualitative risk, or risk score, of mucormycosis in harbor porpoises. Risk factors for this disease are unknown in aquatic mammals. In a separate risk factor analysis, potential risk factors such as pollutants, trace metals (e.g., iron), and co-infection with other pathogens (e.g., viruses and Brucella spp.) were examined in mucormycosis cases and noncases using a matched case-control study design, to determine the presence and strength of association of these factors with mucormycosis. Disease severity (gross and histopathology) and exposure scores were multiplied together to obtain the overall risk scores of 9 -16 which corresponded to moderate and severe, respectively. In the risk factor analysis, the factors most strongly associated with a mucormycosis case, relative to a control, were elevated liver iron, decreased blubber thickness, and the decreased ratio of the sum of PCB congeners/sum of PBDE congeners. The results of this study suggest that mucormycosis may pose an inordinately high risk to harbor porpoises (and potentially sympatric species in the Salish Sea such as southern resident killer whales) based on the detected prevalence and the severity of lesions observed at necropsy. However, the risk may be greater on an individual basis compared to the overall population, and is likely related to other factors such as increased POP and heavy metal burdens.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Azole‐resistant Aspergillus fumigatus is highly prevalent in the environment of Vietnam, with marked variability by land use type - Tra‐My N. Duong; Thanh‐Van Le; Khanh‐Linh H. Tran; Phuong‐Tuyen Nguyen; Bich‐Phuong T. Nguyen; Thu‐Anh Nguyen; Huong‐Lan P. Nguyen; Bich‐Ngoc T. Nguyen; Matthew C. Fisher; Johanna Rhodes; Guy Marks; Greg J. Fox; et al. (Environmental Microbiology, 2021)
Summary Azole‐resistant environmental Aspergillus fumigatus presents a threat to public health but the extent of this threat in Southeast Asia is poorly described. We conducted environmental surveillance in the Mekong Delta region of Vietnam, collecting air and ground samples across key land‐use types, and determined antifungal susceptibilities of Aspergillus section Fumigati (ASF) isolates and azole concentrations in soils. Of 119 ASF isolates, 55% were resistant (or non‐wild type) to itraconazole, 65% to posaconazole and 50% to voriconazole. Azole resistance was more frequent in A. fumigatus sensu stricto isolates (95%) than other ASF species (32%). Resistant isolates and agricultural azole residues were overrepresented in samples from cultivated land. cyp51A gene sequence analysis showed 38/56 resistant A. fumigatus sensu stricto isolates carried known resistance mutations, with TR 34 /L98H most frequent (34/38).

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Conceptualizing social-ecological drivers of change in urban forest patches - Lea R. Johnson; Michelle L. Johnson; Myla F. J. Aronson; Lindsay K. Campbell; Megan E. Carr; Mysha Clarke; Vincent D’Amico; Lindsay Darling; Tedward Erker; Robert T. Fahey; Kristen L. King; Katherine Lautar; et al. (Urban Ecosystems, 2021)

An inventory and typology of permanent floodplain lakes in the Mississippi Alluvial Valley: a first step to conservation planning - L. E. Miranda; M. C. Rhodes; Y. Allen; K. J. Killgore (Aquatic Sciences, 2021)

The Emergence of Mucormycosis in Free-Ranging Marine Mammals of the Pacific Northwest - Jessica L. Huggins; Michael M. Garner; Stephen A. Raverty; Dyanna M. Lambourn; Stephanie A. Norman; Linda D. Rhodes; Joseph K. Gaydos; Jennifer K. Olson; Martin Haulena; M. Bradley Hanson (Frontiers in Marine Science, 2020)

Checklist of the planktonic marine dinoflagellates of New Zealand - Lesley L. Rhodes; Kirsty F. Smith; Lincoln MacKenzie; Catherine Moisan (New Zealand Journal of Marine and Freshwater Research, 2020)
Planktonic dinoflagellate records for New Zealand are substantial due to intense monitoring programmes that have taken place on behalf of New Zealand’s biotoxin regulators and the shellfish industry since 1993. At that time a Karenia bloom caused human illnesses and shellfish harvesting ceased until monitoring was instigated. Phytoplankton records are based on morphological identification using light microscopy but are backed up by government funded research programmes which implement techniques such as electron microscopy, DNA sequencing, molecular detection assays and high throughput sequencing of environmental DNA. This checklist will support management of aquaculture industries, recreational shellfish harvests and environmental health initiatives. Some genera are considered benthic or epiphytic, but have lengthy planktonic life stages. Forty‐five genera in the class Dinophyceae Fritsch are reported: Akashiwo , Alexandrium, Amphidinium, Amylax, Azadinium, Biecheleria, Bysmatrum, Cachonina, Cochlodinium (synonym: Margalefidinium ), Coolia, Dicroerisma, Dinophysis, Diploneis, Diplopsalis, Fragilidium, Glenodinium, Gonyaulax, Gymnodinium, Gyrodinium, Heterocapsa, Karenia, Karlodinium, Lepidodinium, Lingulodinium, Margalefidinium, Ostreopsis, Oxyphysis, Pelagodinium, Pentapharsodinium, Phalacroma, Podolampas, Polarella, Polykrikos, Prorocentrum, Protodinium, Protoodinium, Protoperidinium, Pseliodinium, Scrippsiella, Takayama, Togula, Torodinium, Tripos, Vulcanodinium, Wolosynska. Other genera belonging to the Infraphylum Dinoflagellata also occur in New Zealand waters. They are not in the list but include Noctiluca, Pronoctiluca and Spatulodinium (Class: Noctilucophyceae) and Oxyrrhis (Class: Oxyrrhidophyceae).

A Qualitative Systematic Review of Cigarette Smoking Cessation Interventions for Persons Living with HIV - Lilli Mann-Jackson; David Choi; Erin L. Sutfin; Eunyoung Y. Song; Kristie L. Foley; Aimee M. Wilkin; Caryn G. Morse; Nicole F. Rojas; Timothy S. Oh; Scott D. Rhodes (Journal of Cancer Education, 2019)

Spatio-temporal genetic variation of juvenile smooth hammerhead sharks in South Africa - Gibbs Kuguru; Enrico Gennari; Sabine Wintner; Matthew L. Dicken; Juliana D. Klein; Clint Rhode; Aletta E. Bester-van der Merwe (Marine Biology Research, 2019)

Forecasting species range dynamics with process‐explicit models: matching methods to applications - Natalie J. Briscoe; Jane Elith; Roberto Salguero‐Gómez; José J. Lahoz‐Monfort; James S. Camac; Katherine M. Giljohann; Matthew H. Holden; Bronwyn A. Hradsky; Michael R. Kearney; Sean M. McMahon; Ben L. Phillips; Tracey J. Regan; et al. (Ecology Letters, 2019)
Knowing where species occur is fundamental to many ecological and environmental applications. Species distribution models (SDMs) are typically based on correlations between species occurrence data and environmental predictors, with ecological processes captured only implicitly. However, there is a growing interest in approaches that explicitly model processes such as physiology, dispersal, demography and biotic interactions. These models are believed to offer more robust predictions, particularly when extrapolating to novel conditions. Many process–explicit approaches are now available, but it is not clear how we can best draw on this expanded modelling toolbox to address ecological problems and inform management decisions. Here, we review a range of process–explicit models to determine their strengths and limitations, as well as their current use. Focusing on four common applications of SDMs – regulatory planning, extinction risk, climate refugia and invasive species – we then explore which models best meet management needs. We identify barriers to more widespread and effective use of process‐explicit models and outline how these might be overcome. As well as technical and data challenges, there is a pressing need for more thorough evaluation of model predictions to guide investment in method development and ensure the promise of these new approaches is fully realised.

Occurrence of pathogens in Pacific lamprey (Entosphenus tridentatus) - Aaron D. Jackson; Mary L. Moser; Sam T. Onjukka; Scott LaPatra; Kenneth M. Lujan; Corie Samson; Melissa G. White; Marilyn Blair; Linda Rhodes; Ralph Lampman; Alexa N. Maine; Jeffrey C. Jolley (Reviews in Fish Biology and Fisheries, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

A late Wisconsin (32–10k cal a BP) history of pluvials, droughts and vegetation in the Pacific south‐west United States (Lake Elsinore, CA) - M. E. Kirby; L. Heusser; C. Scholz; R. Ramezan; M. A. Anderson; B. Markle; E. Rhodes; K. C. Glover; J. Fantozzi; C. Hiner; B. Price; H. Rangel (Journal of Quaternary Science, 2018)
Continuous, sub‐centennially resolved, paleo terrestrial records are rare from arid environments such as the Pacific south‐west United States. Here, we present a multi‐decadal to centennial resolution sediment core (Lake Elsinore, CA) to reconstruct late Wisconsin pluvials, droughts and vegetation. In general, the late Wisconsin is characterized by a wetter and colder climate than during the Holocene. Specifically, conditions between 32.3 and 24.9k cal a BP are characterized by large‐amplitude hydrologic and ecologic variability. Highlighting this period is a ∼2000‐year glacial mega‐drought (27.6–25.7k cal a BP) during which the lake shallowed (3.2–4.5 m depth). This period is approximately coeval with a Lake Manix regression and an increase in xeric vegetation in the San Bernardino Mountains (Baldwin Lake). The Local Last Glacial Maximum (LLGM) is bracketed between 23.3 and 19.7k cal a BP − a ∼3000‐year interval characterized by reduced run‐off (relative to the glacial), colder conditions and vegetative stability. Maximum sustained wetness follows the LLGM, beginning at 19.7 and peaking by 14.4k cal a BP. A two‐step decrease in runoff characterizes the Lateglacial to Holocene transition; however, the vegetation change is more complex, particularly at the beginning of the Younger Dryas chronozone. By 12.6–12.4k cal a BP, the climate achieved near Holocene conditions.

A systematic surveillance programme for infectious salmon anaemia virus supports its absence in the Pacific Northwest of the United States - L L Gustafson; L H Creekmore; K R Snekvik; J A Ferguson; J V Warg; M Blair; T R Meyers; B Stewart; K I Warheit; J Kerwin; A E Goodwin; L D Rhodes; et al. (Journal of Fish Diseases, 2018)
In response to reported findings of infectious salmon anaemia virus ( ISAV ) in British Columbia ( BC ), Canada, in 2011, U.S. national, state and tribal fisheries managers and fish health specialists developed and implemented a collaborative ISAV surveillance plan for the Pacific Northwest region of the United States. Accordingly, over a 3‐1/2‐year period, 4,962 salmonids were sampled and successfully tested by real‐time reverse‐transcription PCR . The sample set included multiple tissues from free‐ranging Pacific salmonids from coastal regions of Alaska and Washington and farmed Atlantic salmon ( Salmo salar L.) from Washington, all representing fish exposed to marine environments. The survey design targeted physiologically compromised or moribund animals more vulnerable to infection as well as species considered susceptible to ISAV . Samples were handled with a documented chain of custody and testing protocols, and criteria for interpretation of test results were defined in advance. All 4,962 completed tests were negative for ISAV RNA . Results of this surveillance effort provide sound evidence to support the absence of ISAV in represented populations of free‐ranging and marine‐farmed salmonids on the northwest coast of the United States.

The dinoflagellate genera Gambierdiscus and Ostreopsis from subtropical Raoul Island and North Meyer Island, Kermadec Islands - Lesley L. Rhodes; Kirsty F. Smith; Arjun Verma; Sam Murray; D. Tim Harwood; Tom Trnski (New Zealand Journal of Marine and Freshwater Research, 2017)
An expedition to North Meyer Island, Kermadec Islands, in November 2015, resulted in the isolation of two Gambierdiscus species, G. australes and a previously unknown Gambierdiscus species maintained in the Cawthron Institute Culture Collection of Micro‐algae as CAWD242. Identifications were based on morphology and DNA sequence data analysis. Nine isolates of G. australes produced maitotoxin‐1 (MTX‐1) ranging from present (detectable but below the confidence level) to 36.6 pg per cell. One further isolate did not produce MTX‐1, but all G. australes isolates produced putative MTX‐3. Isolate CAWD242 was negative for MTX‐1 but produced MTX‐3. Ostreopsis sp. 3 isolated from samples collected during an earlier expedition in 2013 produced low concentrations of palytoxin (PLTX)‐like compounds (0.013 pg per cell), but an isolate of the same species from samples collected in 2015 was non‐toxic. Other dinoflagellates isolated and identified were Coolia malayensis , Amphidinium carterae and Prorocentrum hoffmannianum .

Assessment of the metabarcoding approach for community analysis of benthic‐epiphytic dinoflagellates using mock communities - Kirsty F. Smith; Gurjeet S. Kohli; Shauna A. Murray; Lesley L. Rhodes (New Zealand Journal of Marine and Freshwater Research, 2017)
In this study, we assessed the use of DNA metabarcoding as a method for biodiversity assessment of benthic‐epiphytic dinoflagellate communities and for detecting rare, toxin‐producing taxa. Mock communities and three primer pairs were used to establish the recovery of species signal and quantitative representation of species in the samples, as well as to determine primer biases, bioinformatic filtering steps, and threshold levels. Samples were analysed using high‐throughput sequencing Illumina ™ MiSeq technology. We did not find a relationship between read number and cell abundance for all treatments. However, the method was extremely sensitive, with two of the primer pairs detecting a single cell representing less than 0.001% of the cells in the sample. Benthic and epiphytic dinoflagellate communities were also collected from the Bay of Islands (Northland, New Zealand). Dinophyceae species richness was much higher when samples were analysed using metabarcoding than when analysed by microscopy, and we detected several new taxonomic records for New Zealand.

Abiotic and biotic factors modulate carrion fate and vertebrate scavenging communities - Kelsey L. Turner; Erin F. Abernethy; L. Mike Conner; Olin E. Rhodes; James C. Beasley (Ecology, 2017)
Carrion is a valuable nutrient resource used by a diversity of vertebrates across the globe. However, vertebrate scavenging ecology remains an understudied area of science, especially in regards to how biotic and abiotic factors influence scavenging community composition. Here we elucidate how fundamental biotic and abiotic factors interact to modulate the efficiency and composition of vertebrate scavengers by investigating scavenging dynamics across a large gradient in carcass sizes and habitat types representative of many temperate ecosystems, as well as between two seasons reflecting differences in invertebrate activity. We found carcass size and season influenced carcass fate and persistence, as well as the richness and composition of vertebrate scavenger communities utilizing carrion resources. Species richness, which increased as carcass size increased and was higher during the cool season, had a significant effect on carcass persistence. In addition, habitat type influenced carcass detection times by vertebrates, and we observed relatively distinct scavenging communities associated with carcasses of differing sizes. This research highlights a pervasive limitation to the interpretation of results of previous studies as research failing to incorporate carcass size and habitat type could result in the over or underrepresentation of vertebrate scavengers in food web dynamics.

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Brown tree snake (Boiga irregularis) population density and carcass locations following exposure to acetaminophen - Joshua B. Smith; Kelsey L. Turner; James C. Beasley; Travis L. DeVault; William C. Pitt; Olin E. Rhodes (Ecotoxicology, 2016)

The Cawthron Institute Culture Collection of Micro‐algae: a significant national collection - L Rhodes; KF Smith; L MacKenzie; SA Wood; K Ponikla; DT Harwood; M Packer; R Munday (New Zealand Journal of Marine and Freshwater Research, 2016)
The Cawthron Institute Culture Collection of Micro‐algae (CICCM) is a unique, nationally and internationally significant collection of 450 strains of approximately 100 micro‐algae and 50 cyanobacteria species, both living and cryopreserved. The collection comprises 13 taxonomic classes and underpins research into the ecology and taxonomy of the isolates and the biotoxins they produce and their toxicity. The CICCM expanded significantly in the 1990s after a major harmful algae bloom event in the Hauraki Gulf, New Zealand. Since 2000, it has underpinned development of molecular detection tools and enabled development of new chemical testing methods for biotoxins in seafood. The tropical collection allows research into potential issues for New Zealand as the oceans warm, for example, the risks of ciguatera fish poisoning and palytoxins in seafood. Research results generated from isolates in the cyanobacterial collection have assisted national risk management regarding drinking water and informed the development of the New Zealand guidelines for managing cyanobacteria in recreational fresh waters. The actual living and cryopreserved micro‐algae and cyanobacteria collection (without infrastructure) has a current estimated value of NZ$1.6 million.

Growth and reproduction of the highfin grouper Epinephelus maculatus - K. L. Rhodes; B. M. Taylor; D. Hernandez‐Ortiz; J. Cuetos‐Bueno (Journal of Fish Biology, 2016)
Highfin grouper Epinephelus maculatus sampled in Chuuk, Micronesia, exhibited a moderate growth rate and a relatively short life span compared to other epinephelids of a similar size. Combined gonad and otolith analysis provide preliminary evidence that the species conforms to a protogynous sexual pattern. Mean total length at maturity for females was 308 mm with first age at maturity 2·8 years for females and 4 years for males, which differs from other regional studies. Based on the gonado‐somatic index and microscopic analysis of gonads, E. maculatus in Chuuk have a 4 month spawning season (January to April) that corresponds with seasonal lows in sea surface water temperature and overlaps with that of other aggregating epinephelids. The estimated von Bertalanffy growth factor ( K ) was 0·51 year −1 , while total mortality was 0·34 year −1 . Current management for E. maculatus in Chuuk includes a January to May catch, sale and export ban, which overlaps with its reproductive season. The effectiveness of these arrangements will require on‐going monitoring to determine whether alternative management strategies are required to ensure population persistence.

Increasing Cervical Cancer Screening Among US Hispanics/Latinas: A Qualitative Systematic Review - Lilli Mann; Kristie L. Foley; Amanda E. Tanner; Christina J. Sun; Scott D. Rhodes (Journal of Cancer Education, 2015)

Development of eight polymorphic microsatellite markers in the Black and Rufous sengi, Rhynchocyon petersi - Christopher A. Sabuni; Natalie Van Houtte; Samwel L. S. Maganga; Rhodes H. Makundi; Herwig Leirs; Joëlle Goüy de Bellocq (Conservation Genetics Resources, 2015)

Novel and toxin‐producing epiphytic dinoflagellates isolated from sub‐tropical Raoul Island, Kermadec Islands group - L Rhodes; K Smith; T Harwood; C Bedford (New Zealand Journal of Marine and Freshwater Research, 2014)
Epiphytic dinoflagellates were isolated from samples collected from macroalgae and corals during an expedition to the Kermadec Islands group, led by the Auckland Museum in November 2013. Isolates included species of Gambierdiscus and Ostreopsis , genera included in the ciguatera fish poisoning complex. Cells of a compressed (apical to antapical) form of Gambierdiscus were isolated into growth media, but species identification was not possible as isolates failed to grow in culture. The Ostreopsis isolate was successfully cultured and appears to be a new species (a full description will be undertaken). Palytoxin production was determined by chemical analysis (LC‐MS/MS) as 0.013 pg palytoxin equiv. per cell. Prorocentrum isolates were identified morphologically as P . cf. emarginatum and P. lima ; both were non‐toxic. Amphidinium cf. massartii and Coolia malayensis were identified by DNA sequence analysis. The suite of dinoflagellates isolated was typical of the co‐occurring genera found throughout the Pacific region.

Spatial, temporal, and environmental dynamics of a multi-species epinephelid spawning aggregation in Pohnpei, Micronesia - K. L. Rhodes; R. S. Nemeth; E. Kadison; E. Joseph (Coral Reefs, 2014)

Age‐based demographic and reproductive assessment of orangespine Naso lituratus and bluespine Naso unicornis unicornfishes - B. M. Taylor; K. L. Rhodes; A. Marshell; J. L. McIlwain (Journal of Fish Biology, 2014)
Bluespine unicornfish Naso unicornis and orangespine unicornfish Naso lituratus were sampled in Pohnpei and Guam, Micronesia, over 13 months to identify reproductive and age‐based demographic features necessary for informed management. Age and reproductive information were derived from analysis of sagittal otoliths and gonads. Both species had moderate life spans [maximum ages of 23 ( N. unicornis ) and 14 years ( N. lituratus )] compared with published estimates of conspecifics from other locations (>30 years) and of other Naso species. Length at maturation for N. unicornis was similar between Pohnpei and Guam while females consistently matured at a larger size [ c. 30 cm fork length ( L F )] than males ( c. 27 cm L F ). This sex‐specific pattern was reversed in N. lituratus for which estimates of maturation length (females: 15 cm L F ; males: 18 cm L F ) were only obtained from Guam. Developmental patterns in female gonads of both species suggested that initiation of maturation occurs very early. Growth patterns of N. lituratus displayed rapid asymptotic growth compared with N. unicornis and other congeners as well as slight sex‐specific patterns of length‐at‐age. Results highlight the considerable spatial variation that may occur in the population biology of these species across various scales. Additionally, proper management remains complicated without improved knowledge of fishery trends and reproductive behaviour in unicornfishes, species that are prime fishery targets in Micronesia and elsewhere.

The rulB gene of plasmid pWW 0 is a hotspot for the site‐specific insertion of integron‐like elements found in the chromosomes of environmental P seudomonas fluorescens group bacteria - Glenn Rhodes; Hester Bosma; David Studholme; Dawn L. Arnold; Robert W. Jackson; Roger W. Pickup (Environmental Microbiology, 2014)
Summary The rulAB operon of P seudomonas spp. confers fitness traits on the host and has been suggested to be a hotspot for insertion of mobile elements that carry avirulence genes. Here, for the first time, we show that rulB on plasmid pWW 0 is a hotspot for the active site‐specific integration of related integron‐like elements ( ILE s) found in six environmental pseudomonads (strains FH 1– FH 6). Integration into rulB on pWW 0 occurred at position 6488 generating a 3 bp direct repeat. ILE s from FH 1 and FH 5 were 9403 bp in length and contained eight open reading frames ( ORF s), while the ILE from FH 4 was 16 233 bp in length and contained 16 ORF s. In all three ILE s, the first 5.1 kb (containing ORF s 1–4) were structurally conserved and contained three predicted site‐specific recombinases/integrases and a tetR homologue. Downstream of these resided ORF s of the ‘variable side’ with structural and sequence similarity to those encoding survival traits on the fitness enhancing plasmid pGRT 1 ( ILE FH 1 and ILE FH 5 ) and the NR‐II virulence region of genomic island PAGI ‐5 ( ILE FH 4 ). Collectively, these ILEs share features with the previously described type III protein secretion system effector ILEs and are considered important to host survival and transfer of fitness enhancing and (a)virulence genes between bacteria.

Reducing Livestock Effects on Public Lands in the Western United States as the Climate Changes: A Reply to Svejcar et al - Robert L. Beschta; Debra L. Donahue; Dominick A. DellaSala; Jonathan J. Rhodes; James R. Karr; Mary H. O’Brien; Thomas L. Fleischner; Cindy Deacon Williams (Environmental Management, 2014)

Gambierdiscus cf. yasumotoi (Dinophyceae) isolated from New Zealand's sub‐tropical northern coastal waters - L Rhodes; G Giménez Papiol; K Smith; T Harwood (New Zealand Journal of Marine and Freshwater Research, 2014)
A globular form of the epiphytic dinoflagellate genus, Gambierdiscus , was isolated and cultured from Northland, New Zealand. The closest species, based on Bayesian analyses of the large subunit ribosomal DNA (LSU rDNA) D1‐D3 and D8‐D10 regions, were G. yasumotoi and G. ruetzleri . The thecal plate morphology of the isolate, in particular the small pores and large 2’’’’ plate, most closely resembled G. yasumotoi . However, the ratios of the cell measurements (depth‐to‐width 1.3 and length‐to‐width 1.4) were more similar to G. ruetzleri and suggest that morphological variability exists within the globular Gambierdiscus group. The isolate produced putative maitotoxin‐3, but no maitotoxin‐1 or ciguatoxin.

The genus Pseudo‐nitzschia (Bacillariophyceae) in New Zealand: analysis of the last decade's monitoring data - L Rhodes; W Jiang; B Knight; J Adamson; K Smith; V Langi; M Edgar (New Zealand Journal of Marine and Freshwater Research, 2013)
The diatom genus Pseudo‐nitzschia blooms throughout New Zealand's coastal waters. More than a decade of monitoring data were analysed in this study and seasonality was a significant factor in the appearance of Pseudo‐nitzschia blooms. Austral spring and summer were the main bloom periods, although there were regional differences. Between January 2000 and August 2011, 8.4% of 29,000 seawater samples analysed for Pseudo‐nitzschia exceeded the voluntary trigger level for biotoxin testing (10×10 4 cells l −1 ), and these were analysed by fluorescent in situ hybridisation (FISH) assays. Pseudo‐nitzschia fraudulenta and P. pseudodelicatissima (low domoic acid [DA] producers) were the dominant bloom formers throughout New Zealand (each contributing 25%) followed by the highly toxic P. australis (10%). Shellfish flesh testing for DA was triggered on 8477 occasions between 2000 and 2011, but no samples exceeded the regulatory limit (20 mg/kg); the maximum concentration was 13 mg/kg (Marlborough Sounds, mid‐winter 2010).

Eleven microsatellite markers for the eastern gray squirrel (Sciurus carolinensis) and their utility in eastern fox squirrels (Sciurus niger) and red squirrels (Tamiasciurus hudsonicus) - Jennifer A. Fike; Cecilia A. Hennessy; Michael L. Kennedy; Olin E. Rhodes (Conservation Genetics Resources, 2013)

Use of Experimental Translocations of Allegheny Woodrat to Decipher Causal Agents of Decline - TIMOTHY J. SMYSER; SCOTT A. JOHNSON; L. KRISTEN PAGE; CASSIE M. HUDSON; OLIN E. RHODES (Conservation Biology, 2013)
Translocations are an important tool for wildlife conservation, although progress in the field of reintroduction biology has been hindered by the ad hoc and opportunistic nature of many translocations. We used an experimental translocation to elucidate the role of raccoon roundworm ( Baylisascaris procyonis ) and inbreeding depression in the decline of the Allegheny woodrat ( Neotoma magister ), an endangered species. We translocated woodrats from genetically diverse populations in the core of the species range to 4 previously occupied sites (reintroductions) and 2 sites supporting genetically depauperate populations (reinforcements) in Indiana (U.S.A.). In 2 reintroduction sites and 1 reinforcement site, we distributed anthelmintic baits to passively deworm raccoons and reduce the risk of woodrat exposure to roundworms. The remaining sites served as controls. We used raccoon latrine surveys and fecal flotation to monitor temporal variability in roundworm prevalence and effect of treatment. We used live trapping and microsatellite genotyping to monitor the demographic and genetic response of translocated populations over the following 54 months. At the conclusion of the study, 4 of 6 translocations were successfully maintaining abundance through local recruitment. The distribution of anthelmintic baits reduced levels of roundworm contamination, but levels of contamination were also low in 2 of 3 control sites. Reintroductions failed at control sites, one of which was due to high roundworm exposure. The other failed control reintroduction was likely attributable to demographic stochasticity and limited reproductive potential following initial mortality within the first 4 months. In both control and treatment reinforcements, increases in both allelic richness and heterozygosity were accompanied by increases in abundance, which is suggestive of genetic rescue. Our results demonstrate that mitigation of roundworm exposure through the distribution of anthelmintic baits can facilitate woodrat recovery and that diversity within genetically depauperate populations can be restored through the introduction of a limited number of individuals . El Uso de Reubicaciones Experimentales de Neotoma magister para Descifrar Agentes Causales de Disminución

Fishing groupers towards extinction: a global assessment of threats and extinction risks in a billion dollar fishery - Yvonne Sadovy de Mitcheson; Matthew T Craig; Athila A Bertoncini; Kent E Carpenter; William W L Cheung; John H Choat; Andrew S Cornish; Sean T Fennessy; Beatrice P Ferreira; Philip C Heemstra; Min Liu; Robert F Myers; et al. (Fish and Fisheries, 2013)
Groupers are a valuable fishery resource of reef ecosystems and are among those species most vulnerable to fishing pressure because of life history characteristics including longevity, late sexual maturation and aggregation spawning. Despite their economic importance, few grouper fisheries are regularly monitored or managed at the species level, and many are reported to be undergoing declines. To identify major threats to groupers, the International Union for Conservation of Nature (IUCN) Red List criteria were applied to all 163 species. Red List assessments show that 20 species (12%) risk extinction if current trends continue, and an additional 22 species (13%) are considered to be Near Threatened. The Caribbean Sea, coastal Brazil and Southeast Asia contain a disproportionate number of Threatened species, while numerous poorly documented and Near Threatened species occur in many regions. In all, 30% of all species are considered to be Data Deficient. Given that the major threat is overfishing, accompanied by a general absence and/or poor application of fishery management, the prognosis for restoration and successful conservation of Threatened species is poor. We believe that few refuges remain for recovery and that key biological processes (e.g. spawning aggregations) continue to be compromised by uncontrolled fishing. Mariculture, through hatchery‐rearing, increases production of a few species and contributes to satisfying high market demand, but many such operations depend heavily on wild‐caught juveniles with resultant growth and recruitment overfishing. Better management of fishing and other conservation efforts are urgently needed, and we provide examples of possible actions and constraints.

Reproductive biology of squaretail coralgrouper Plectropomus areolatus using age‐based techniques - K. L. Rhodes; B. M. Taylor; C. B. Wichilmel; E. Joseph; R. J. Hamilton; G. R. Almany (Journal of Fish Biology, 2013)
The squaretail coralgrouper Plectropomus areolatus was identified as a fast‐growing, early maturing and relatively short‐lived aggregation‐spawning epinephelid. Examinations of sectioned otoliths found females and males first maturing at 2 and 3 years, respectively, suggesting protogynous hermaphroditism; however, no transitionals were observed in samples. Age distribution for the two sexes was similar and both were represented in the oldest age class; however, significant sex‐specific differences in size‐at‐age were identified. Both sexes fully recruit into the fishery at age 4 years and reach 90% of asymptotic length by age 3 years. Underwater visual assessments, combined with the gonado‐somatic indices, revealed a 5 month reproductive season, with interannual variability observed in the month of highest density within the spawning aggregation. Catch restrictions on adults during spawning times and at reproductive sites, combined with gear‐based management and enhanced enforcement, are recommended to maintain spawning stocks. Based on the available evidence, the sexual pattern for this species is unresolved.

Molecular genetic tools for environmental monitoring of New Zealand's aquatic habitats, past, present and the future - SA Wood; KF Smith; JC Banks; LA Tremblay; L Rhodes; D Mountfort; SC Cary; X Pochon (New Zealand Journal of Marine and Freshwater Research, 2013)
The assessment of biological samples is critical for measuring the ‘health’ of New Zealand aquatic environments. Analysis of these samples commonly requires species identification and enumeration, which usually involves microscopy or microbiological methods. These techniques can be time‐consuming, laborious, and are dependent on taxonomic expertise. Recent advances in molecular methods provide promising tools for assessing environmental samples. A range of molecular techniques are now used in New Zealand including: fluorescent in situ hybridisation; automated ribosomal intergenic spacer analysis; quantitative polymerase chain reaction; and, most recently, next‐generation sequencing. The organisms (or targets) and environments monitored are equally diverse, ranging from cyanobacteria, rotifers and invasive fish in lakes, to macroinvertebrates, and biofilm communities in rivers, to bacteria, micro‐ and macro‐algae and invertebrates in marine ecosystems. Despite research and validation demonstrating their potential, the application of these tools by monitoring agencies has been limited. Legislative requirements, costs, and a reluctance to change methodologies, are the most likely reasons for this. This review examines molecular tools that have been previously or are currently used for monitoring aquatic environments in New Zealand, and explores how these, and new techniques, may be applied in the future.

Adapting to Climate Change on Western Public Lands: Addressing the Ecological Effects of Domestic, Wild, and Feral Ungulates - Robert L. Beschta; Debra L. Donahue; Dominick A. DellaSala; Jonathan J. Rhodes; James R. Karr; Mary H. O’Brien; Thomas L. Fleischner; Cindy Deacon Williams (Environmental Management, 2013)

The effects of varenicline on attention and inhibitory control among treatment-seeking smokers - Jessica D. Rhodes; Larry W. Hawk; Rebecca L. Ashare; Nicolas J. Schlienz; Martin C. Mahoney (Psychopharmacology, 2012)

Consequences of metapopulation collapse: comparison of genetic attributes between two Allegheny woodrat metapopulations - Timothy J. Smyser; Joseph E. Duchamp; Scott A. Johnson; Jeffery L. Larkin; Olin E. Rhodes (Conservation Genetics, 2012)

Reproductive movement, residency and fisheries vulnerability of brown-marbled grouper, Epinephelus fuscoguttatus (Forsskål, 1775) - K. L. Rhodes; J. McIlwain; E. Joseph; R. S. Nemeth (Coral Reefs, 2012)

The toxic effects of three dinoflagellate species from the genus Karenia on invertebrate larvae and finfish - F Shi; P McNabb; L Rhodes; P Holland; S Webb; J Adamson; A Immers; R Gooneratne; J Holland (New Zealand Journal of Marine and Freshwater Research, 2012)
Three species of Kareniaceae, Karenia brevis , Karenia brevisulcata and Karenia mikimotoi were assessed for toxicity to juvenile Chinook salmon ( Oncorhynchus tshawytscha ), snapper ( Pagrus auratus ) and six species of marine invertebrate larvae (Greenshell TM mussel, pacific oyster, paua [New Zealand abalone], sea slug, sea urchin and brine shrimp). Karenia brevis was ichthyotoxic to juvenile salmon with a LT 50 of 0.75 h at 0.18 × 10 6 cells L –1 but juvenile snapper were less sensitive (LT 50 of 4.5 h at 5.9 × 10 6 cells L –1 ). Karenia brevisulcata also showed differential toxicity to juvenile salmon and snapper with LT 50 of 0.48 h at 11 × 10 6 cells L –1 and 7.5 h at 16 × 10 6 cells L –1 respectively. However, no acute symptoms were observed in the fish following 48 h exposure to K. mikimotoi at 3.4 × 10 6 cells L –1 . Karenia brevis at the highest level tested (8.7 × 10 6 cells L –1 ) did not cause observable symptoms in any of the invertebrate larvae over 24 h. Karenia mikimotoi only affected paua larvae (LT 50 10 h at 12 × 10 6 cells L –1 ). Karenia brevisulcata was highly toxic to mussel, sea urchin and paua larvae (LT 50 1–6.1 h at 7.5–9.6 × 10 6 cells L –1 ), toxic to sea slug and oyster larvae (LT 50 6 h at 80 × 10 6 cells L –1 and 9.2 h at 34 × 10 6 cells L –1 respectively) but did not affect brine shrimp. Analysis of test cultures by liquid chromatography‐mass spectrometry confirmed that K. brevis produced brevetoxins (52 pg cell –1 ; mainly brevetoxin‐2). Karenia brevisulcata produced brevisulcatic acids (BSXs) and the more toxic Karenia brevisulcata toxins (KBTs). Karenia mikimotoi did not produce brevetoxin, BSXs or KBTs. The present study confirms the broad threats that blooms of K. brevisulcata pose to marine ecosystems and aquaculture, and the hazards of K. brevis to finfish and K. mikimotoi to abalone respectively.

Pneumococcal antigen testing of blood culture broth to enhance the detection of Streptococcus pneumoniae bacteremia - H. C. Baggett; J. Rhodes; S. Dejsirilert; P. Salika; T. Wansom; P. Jorakate; A. Kaewpan; S. J. Olsen; S. A. Maloney; L. F. Peruski (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Commercial coral-reef fisheries across Micronesia: A need for improving management - P. Houk; K. Rhodes; J. Cuetos-Bueno; S. Lindfield; V. Fread; J. L. McIlwain (Coral Reefs, 2012)

Production of pinnatoxins E, F and G by scrippsielloid dinoflagellates isolated from Franklin Harbour, South Australia - L Rhodes; K Smith; A Selwood; P McNabb; S Molenaar; R Munday; C Wilkinson; G Hallegraeff (New Zealand Journal of Marine and Freshwater Research, 2011)
A pinnatoxin producing dinoflagellate was isolated in cyst form from sediments from Franklin Harbour, South Australia, December 2009. One isolate (CAWD180) produced pinnatoxin G, E, F and A (87, 10, 41 and 1.3 pg/cell respectively; liquid chromatograph–mass spectrometer, LC‐MS, analysis) and another (CAWD183) produced pinnatoxin G only (13 pg/cell). Australian strains were identical to pinnatoxin E and F producers isolated from Northland, New Zealand (2008), based on large subunit (LSU) rDNA and ITS spacer region sequence data. Cysts were capable of division and produced more toxin per cell than the excysted motile form. Crude extracts of mass cultures were tested for toxicity in mice by intraperitoneal (i.p.) injection, gavage and voluntary consumption, and toxicity ratios were 1.0:1.8:4.5 (CAWD180) and 1.0:2.9:7.8 (CAWD183). This is similar to the ratios for New Zealand isolates, but differs from other cyclic imines for which oral toxicity can be 10–1000‐fold less than i.p. administration.

Passive acoustic telemetry reveals highly variable home range and movement patterns among unicornfish within a marine reserve - A. Marshell; J. S. Mills; K. L. Rhodes; J. McIlwain (Coral Reefs, 2011)

Research partnerships with local communities: two case studies from Papua New Guinea and Australia - G. R. Almany; R. J. Hamilton; D. H. Williamson; R. D. Evans; G. P. Jones; M. Matawai; T. Potuku; K. L. Rhodes; G. R. Russ; B. Sawynok (Coral Reefs, 2010)

Home range estimates for squaretail coralgrouper, Plectropomus areolatus (Rüppell 1830) - N. Hutchinson; K. L. Rhodes (Coral Reefs, 2010)

Identification of non‐indigenous marine macroalgae from New Zealand aquaria outlets - Kirsty F Smith; Hernando Acosta; Judith E Broom; Lesley L Rhodes (New Zealand Journal of Marine and Freshwater Research, 2010)
Most vector management and research on marine bioinvasions has focused on shipping‐related pathways. More recently, less obvious mechanisms, such as the aquarium trade, have been recognised as important mechanisms for marine invasions, such as for the alga Caulerpa taxifolia . In this study, macroalgal specimens were collected from aquarium shops in Auckland and Nelson. Specimens were initially identified morphologically as C. taxifolia, C. racemoasa, Coelarthrum sp. and Cryptonemia sp. DNA sequencing corroborated the identification of the Caulerpa specimens. DNA sequencing also revealed that a specimen identified as Coelarthrum sp. by morphological features was in fact most probably Chamaebotrys sp. Because of the small number of Cryptonemia sequences in GenBank for comparison, only a tentative identification for this red alga could be made. Our findings of non‐native macroalgae, including C. taxifolia , in aquarium shops in New Zealand show that even strict quarantine procedures cannot completely prevent the importation of non‐indigenous species. Therefore, early detection, which begins with species identification, is essential to design effective control and eradication programmes.

Salt Spray Induces Osmotic Adjustment and Tissue Rigidity in Smooth Cordgrass, Spartina alterniflora (Loisel.) - Brant W. Touchette; Kirsten L. Rhodes; Gracen A. Smith; Mariana Poole (Estuaries and Coasts, 2009)

Development of twenty-five polymorphic microsatellite markers for the endangered red-cockaded woodpecker (Picoides borealis) - Jennifer A. Fike; Giri Athrey; Reed Bowman; Paul L. Leberg; Olin E. Rhodes (Conservation Genetics, 2009)

Maintenance of cyanotoxin production by cryopreserved cyanobacteria in the New Zealand culture collection - Susanna A. Wood; Lesley L. Rhodes; Serean L. Adams; Janet E. Adamson; Kirsty F. Smith; John F. Smith; H. Robin Tervit; S. Craig Cary (New Zealand Journal of Marine and Freshwater Research, 2008)
A culture collection of freshwater planktonic and benthic cyanobacteria collected from sites across New Zealand has been established at the Cawthron Institute, Nelson, New Zealand. Limited resources led to uncertainty regarding the long‐term maintenance of this collection. The present study demonstrates cryopreservation to be a viable method for long‐term storage of cyanobacteria. Seventeen of 20 strains evaluated were successfully cryopreserved using the permeating cryopreservation agent dimethyl sulfoxide (Me 2 SO), at a final concentration of 15% (v/v). Cyanotoxin analysis was undertaken on selected strains known to produce microcystins, nodularin, anatoxin‐a, and saxitoxins. All strains retained their ability to produce these toxins following cryopreservation.

Electron spin resonance dating of South Australian megafauna sites - R. Grün; R. Wells; S. Eggins; N. Spooner; M. Aubert; L. Brown; E. Rhodes (Australian Journal of Earth Sciences, 2008)

Fine-mapping the genetic basis of CRP regulation in African Americans: a Bayesian approach - Benjamin Rhodes; David L. Morris; Lakshman Subrahmanyan; Cristin Aubin; Carlos F. Mendes de Leon; Jeremiah F. Kelly; Dennis A. Evans; John C. Whittaker; Jorge R. Oksenberg; Philip L. De Jager; Tim J. Vyse (Human Genetics, 2008)

Characterization and management of the commercial sector of the Pohnpei coral reef fishery, Micronesia - K. L. Rhodes; M. H. Tupper; C. B. Wichilmel (Coral Reefs, 2008)

Historical and contemporary evidence of a mutton snapper (Lutjanus analis Cuvier, 1828) spawning aggregation fishery in decline - R. T. Graham; R. Carcamo; K. L. Rhodes; C. M. Roberts; N. Requena (Coral Reefs, 2008)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

A preliminary market-based analysis of the Pohnpei, Micronesia, grouper (Serranidae: Epinephelinae) fishery reveals unsustainable fishing practices - K. L. Rhodes; M. H. Tupper (Coral Reefs, 2007)

Hypolithic community shifts occur as a result of liquid water availability along environmental gradients in China's hot and cold hyperarid deserts - Stephen B. Pointing; Kimberley A. Warren‐Rhodes; Donnabella C. Lacap; Kevin L. Rhodes; Christopher P. McKay (Environmental Microbiology, 2007)
Summary Hypolithic cyanobacterial communities occur in hot and cold hyperarid environments but the physical factors determining their diversity are not well understood. Here we report hypolithic diversity and colonization of a common quartz substrate at several hyperarid locations in the ancient deserts of north‐western China, that experience varying mean annual temperature, rainfall and concomitant availability of liquid water in soil. Microscopy and enrichment culture resulted only in Chroococcidiopsis morphotypes which were ubiquitous, but community phylogenetic analysis revealed considerable cyanobacterial and heterotrophic bacterial diversity. Species Richness and Shannon's Diversity Index displayed a significant positive linear correlation with availability of liquid water but not temperature or rainfall alone. Several taxonomic groups occurred only in specific climatically defined locations, while for Chroococcidiopsis , Deinococcus and Phormidium location specific lineages within these genera were also evident. Multivariate analysis was used to illustrate pronounced community shifts due to liquid water availability, although these did not significantly affect the predicted functional relationships within any given assemblage in either hot or cold, wet or dry hyperarid deserts. This study clearly demonstrates that availability of liquid water, rather than temperature or rainfall per se is the key determinant of hypolithic diversity in hyperarid locations, and furthermore that functionally similar yet taxonomically distinct communities occur, characterized by the presence of taxa that are specific to defined levels of aridity.

A robust set of black walnut microsatellites for parentage and clonal identification - Rodney L. Robichaud; Jeffrey C. Glaubitz; Olin E. Rhodes; Keith Woeste (New Forests, 2006)

The evolving story of Mycobacterium tuberculosis clade members detected in fish - I M Kaattari; M W Rhodes; S L Kaattari; E B Shotts (Journal of Fish Diseases, 2006)
Advances in molecular analyses have permitted documentation of an increasing spectrum of mycobacteria infecting fish. Although some of these mycobacteria are not closely related, several species belong to the Mycobacterium tuberculosis clade. One member of the clade, M. marinum , is well known as an agent of piscine mycobacteriosis. Three other clade species, M. shottsii , M. pseudoshottsii and M. ‘chesapeaki’ , have recently been identified as predominant disease agents in a widespread, continuing epizootic in wild striped bass of the Chesapeake Bay. A fifth clade member, M. ulcerans , has recently been indirectly detected in wild, African cichlid fish. As M. ulcerans is the third most common human mycobacterial infection worldwide, even such indirect evidence of M. ulcerans in fish must be more thoroughly investigated. Complicating the differentiation of these clade members is the growing recognition of intraspecies and interspecies variation in phenotypes, genes and virulence. Thus, researchers must be aware of the variety of piscine isolates within the M. tuberculosis clade. This review summarizes the methods of detection and differentiation for this important group of mycobacteria.

Geographic distribution of Pfiesteria spp. (Pfiesteriaceae) in Tasman Bay and Canterbury, New Zealand (2002–03) - Lesley L. Rhodes; Janet E. Adamson; Parke A. Rublee; Eric Schaefer (New Zealand Journal of Marine and Freshwater Research, 2006)
The fish‐killing heterotrophic dino‐flagellate species Pfiesteria piscicida and P. shumwayae (also Pseudopfiesteria shumwayae ) were present throughout New Zealand and were residents of Tasman Bay's well‐flushed estuaries and Canterbury's brackish lakes, as determined by polymerase chain reaction‐based detection assays. The two species occurred in a wide range of salinities and temperatures, although detection was restricted seasonally from spring through to autumn, except for one incidence in the shallow waters of Wairewa/ Lake Forsyth, Canterbury, in the winter of 2003. The DNA sequencing data indicated that P. shumwayae may encompass a suite of genetically closely related species. The presence of Pfiesteria in New Zealand is not considered an immediate risk to fish or human health given the current low‐to‐moderate nutrient concentrations in New Zealand's estuaries and brackish lakes. However, increases in nutrient loadings could pose a risk, as has occurred in eastern United States estuaries.

International accreditation of sandwich hybridisation assay format DNA probes for micro‐algae - Katie Ayers; Lesley L. Rhodes; John Tyrrell; Melissa Gladstone; Chris Scholin (New Zealand Journal of Marine and Freshwater Research, 2005)
The sandwich hybridisation assay (SHA) is a DNA probe‐based method for rapid identification and enumeration of toxic micro‐algae which uses species specific oligonucleotide probes targeted at ribosomal RNA. It is suited to fragile micro‐algal cells which commonly collapse during the fixation stage of sample collection, compromising identification by traditional microscopy. The assay has been available for research for several years, but was validated and accepted for international accreditation for commercial laboratory use in New Zealand in May 2004 (International Accreditation New Zealand: ISO 17025). During the validation of the raphidophyte assay, some discrepancies were noted between SHA cell concentration estimates and traditional light microscope cell counts. Higher SHA estimates were recorded when blooms had collapsed but rRNA was still present in sea water. Conversely, higher traditional cell counts occurred when sample delivery was delayed more than 48 h, presumably owing to degradation of rRNA in the live cultures used for the SHA. SHA cell concentration estimates of the toxic diatom bloom‐former Pseudo‐nitzschia australis were also compared with whole cell format DNA probe counts and traditional microscope counts; SHA counts were comparable for the three methods tested.

Mutation identification in a canine model of X-linked ectodermal dysplasia - Margret L. Casal; Jennifer L. Scheidt; James L. Rhodes; Paula S. Henthorn; Petra Werner (Mammalian Genome, 2005)

Spawning aggregations of Lutjanus cyanopterus (Cuvier) on the Belize Barrier Reef over a 6 year period - W. D. Heyman; B. Kjerfve; R. T. Graham; K. L. Rhodes; L. Garbutt (Journal of Fish Biology, 2005)
Cubera snapper Lutjanus cyanopterus aggregated to spawn at Gladden Spit, a salient sub‐surface reef promontory seaward of the emergent reef and near the continental shelf edge of Belize. Their spawning aggregations typically formed 2 days before to 12 days after full moon from March to September 1998–2003 within a 45 000 m 2 reef area. Peak abundance of 4000 to 10 000 individuals was observed between April and July each year, while actual spawning was most frequently observed in May. Spawning was observed consistently from 40 min before to 10 min after sunset within a confined area ≤1000 m 2 . Data suggested that cubera snapper consistently formed seasonal spawning aggregations in relation to location, photoperiod, water temperature and lunar cycle, and that spawning was cued by time of day but not tides. The cubera snapper aggregation site was included within the Gladden Spit Marine Reserve, a conditional no‐take fishing zone.

A Comparison of Hybridization between Mottled Ducks (Anas fulvigula)and Mallards (A. platyrhynchos) in Florida and South Carolina using Microsatellite DNA Analysis - Christen L. Williams; Richard C. Brust; Timothy T. Fendley; Gerald R. Tiller; Olin E. Rhodes (Conservation Genetics, 2005)

Gymnodinoid genera Karenia and Takayama (Dinophyceae) in New Zealand coastal waters - Miguel F. de Salas; Lesley L. Rhodes; Lincoln A. Mackenzie; Janet E. Adamson (New Zealand Journal of Marine and Freshwater Research, 2005)
New Zealand has been subject to massive blooms of gymnodinoid dinoflagellates over the last decade and in some instances marine biota mortalities. Respiratory problems for people impacted by aerosols from these blooms have occurred. However, because of the difficulty in definitively identifying gymnodinoid dinoflagellates, the identities of the causative organisms have not always been established with certainty. This paper documents the occurrence of several newly described species in the genera Karenia and Takayama in New Zealand's coastal waters as determined by analysis of DNA sequence data. The species include Karenia umbella de Salas, Bolch & Hallegraeff, Takayama helix de Salas, Bolch, Botes & Hallegraeff, and T. tasmanica de Salas, Bolch & Hallegraeff, which are known to have caused fish kills in Tasmanian (Australia) waters in the past. Liquid chromatography‐mass spectrometry analyses of mass cultures of these dinoflagellates have been negative for neurotoxic brevetoxins. The species designation of several unidentified gymnodinoid species (designated Gymnodinium sp.) isolated from New Zealand waters and maintained in the Cawthron Collection of Micro‐algae were also identified on the basis of their DNA sequences.

Acidity of exogenous metal ion in the activation of calcineurin - David J. Rhode; Bruce L. Martin (BioMetals, 2004)

Postfire Management on Forested Public Lands of the Western United States - ROBERT L. BESCHTA; JONATHAN J. RHODES; J. BOONE KAUFFMAN; ROBERT E. GRESSWELL; G. WAYNE MINSHALL; JAMES R. KARR; DAVID A. PERRY; F. RICHARD HAUER; CHRISTOPHER A. FRISSELL (Conservation Biology, 2004)
Forest ecosystems in the western United States evolved over many millennia in response to disturbances such as wildfires. Land use and management practices have altered these ecosystems, however, including fire regimes in some areas. Forest ecosystems are especially vulnerable to postfire management practices because such practices may influence forest dynamics and aquatic systems for decades to centuries. Thus, there is an increasing need to evaluate the effect of postfire treatments from the perspective of ecosystem recovery. We examined, via the published literature and our collective experience, the ecological effects of some common postfire treatments. Based on this examination, promising postfire restoration measures include retention of large trees, rehabilitation of firelines and roads, and, in some cases, planting of native species. The following practices are generally inconsistent with efforts to restore ecosystem functions after fire: seeding exotic species, livestock grazing, placement of physical structures in and near stream channels, ground‐based postfire logging, removal of large trees, and road construction. Practices that adversely affect soil integrity, persistence or recovery of native species, riparian functions, or water quality generally impede ecological recovery after fire. Although research provides a basis for evaluating the efficacy of postfire treatments, there is a continuing need to increase our understanding of the effects of such treatments within the context of societal and ecological goals for forested public lands of the western United States.

Cloning and expression of pkaC and pkaR, the genes encoding the cAMP-dependent protein kinase of Aspergillus fumigatus - Brian G. Oliver; John C. Panepinto; Jarrod R. Fortwendel; Darcey L. Smith; David S. Askew; Judith C. Rhodes (Mycopathologia, 2002)

Pfiesteria shumwayae (Pfiesteriaceae) in New Zealand - Lesley L. Rhodes; Joann M. Burkholder; Howard B. Glasgow; Parke A. Rublee; Coy Allen; Janet E. Adamson (New Zealand Journal of Marine and Freshwater Research, 2002)
Pfiesteria shumwayae Steidinger et Burkholder is now known to be present in New Zealand and occurs in estuaries around the country. The presence of Pfiesteria was initially determined by a polymerase chain reaction (PCR)‐based detection assay, using oligonucleotide primers targeted at ribosomal DNA extracted from estuarine water and sediments. Presence was confirmed by isolation from fresh sediments in the presence offish (Oreochromis mossambicus) , followed by identification by scanning electron microscopy. The New Zealand isolates of P. shumwayae were ichthyotoxic in bioassays, but there is no historic evidence offish kills in New Zealand associated with the dinoflagellate.

Microsatellite variation in the reintroduced Pennsylvania elk herd - Christen Lenney Williams; Thomas L. Serfass; Rawland Cogan; Olin E. Rhodes (Molecular Ecology, 2002)
Relocation programs have restored elk ( Cervus elaphus ) to portions of its vast historical range. We examine the consequences of these relocation programs by assessing variation at 10 microsatellite loci in three elk herds, a source herd (Yellowstone National Park), a large herd reintroduced from Yellowstone (Custer State Park) and a bottlenecked herd reintroduced from both Yellowstone and Custer (the Pennsylvania herd). Observed single locus heterozygosities ranged from 0.000 to 0.739. Multi‐locus heterozygosities ranged from 0.222 to 0.589. Although significant differences were detected among all three herds, the Yellowstone National Park and Custer State Park herds possessed similar levels of variation and heterozygosity, and the genetic distance between these two herds was small. The Pennsylvania herd, on the other hand, experienced a 61.5% decrease in heterozygosity relative to its source herds, possessed no unique and few rare alleles, and the genetic distances between the Pennsylvania herd and its sources were large. Simulations were performed to identify bottleneck scenarios in agreement with levels of variation in the Pennsylvania herd. Our data confirm that the rate of population growth post‐relocation may have important genetic consequences and indicate that theoretical predictions regarding the maintenance of genetic variation during relocation events must be viewed with caution when small numbers of a polygynous species are released.

Genetic variation across the historical range of the wild turkey ( Meleagris gallopavo ) - K. E. Mock; T. C. Theimer; O. E. Rhodes; D. L. Greenberg; P. Keim (Molecular Ecology, 2002)
Genetic differences within and among naturally occurring populations of wild turkeys ( Meleagris gallopavo ) were characterized across five subspecies’ historical ranges using amplified fragment length polymorphism (AFLP) analysis, microsatellite loci and mitochondrial control region sequencing. Current subspecific designations based on morphological traits were generally supported by these analyses, with the exception of the eastern ( M. g. silvestris ) and Florida ( M. g. osceola ) subspecies, which consistently formed a single unit. The Gould’s subspecies was both the most genetically divergent and the least genetically diverse of the subspecies. These genetic patterns were consistent with current and historical patterns of habitat continuity. Merriam’s populations showed a positive association between genetic and geographical distance, Rio Grande populations showed a weaker association and the eastern populations showed none, suggesting differing demographic forces at work in these subspecies. We recommend managing turkeys to maintain subspecies integrity, while recognizing the importance of maintaining regional population structure that may reflect important adaptive variation.

Temporal and Spatial Trends in Spawning Aggregations of Camouflage Grouper, Epinephelus Polyphekadion, in Pohnpei, Micronesia - Kevin L. Rhodes; Yvonne Sadovy (Environmental Biology of Fishes, 2002)

Pseudo‐nitzschia multistriata (Bacillariophyceae) in New Zealand - Lesley L. Rhodes; Janet Adamson; Chris Scholin (New Zealand Journal of Marine and Freshwater Research, 2000)
Pseudo‐nitzschia multistriata (Takano) Takano has been observed in seawater samples from the North Island and from the northern waters of the South Island, New Zealand, with blooms of >1.0 × 10 6 cells litre ‐1 being recorded in December 1997 (austral summer), and minor blooms occurring in both summer and winter 1998 and 1999. The species is notable for its sigmoid form, and for its cross‐reactivity with oligonucleotide probes targeted at P. australis Frenguelli ribosomal RNA. The species is non‐toxic, and for biotoxin monitoring purposes needs to be discriminated from the highly toxic P. australis . It falls in the “delicatissima” complex of Pseudo‐nitzschia H. Peragallo species, and electron microscopy shows a close resemblance to P. delicatissima (Cleve) Heidin, except for the lack of a central larger interspace.

BTL-II : a polymorphic locus with homology to the butyrophilin gene family, located at the border of the major histocompatibility complex class II and class III regions in human and mouse - M. Stammers; L. Rowen; D. Rhodes; J. Trowsdale; S. Beck (Immunogenetics, 2000)

Microphytobenthic communities of subtidal locations in New Zealand: Taxonomy, biomass, production, and food‐web implications - Paul A. Gillespie; Paul D. Maxwell; Lesley L. Rhodes (New Zealand Journal of Marine and Freshwater Research, 2000)
Diatom mats dominated by large sig‐moid, raphid species of the genus Gyrosigma (Naviculaceae) and, in some instances, the tube‐former, Berkeleya rutilans (Naviculaceae) were observed in the semi‐enclosed coastal waters (depths 6–20 m) of Tory Channel, Marlborough Sounds, New Zealand. The latter species, not previously observed in New Zealand, is generally associated with intertidal environments where light intensities are relatively higher than subtidal locations. Its presence imparted a filamentous nature to the mat that may play a role in maintaining the integrity of the sediment/water interface. Sediment chlorophyll a concentrations ranged from c. 20 to 200 mg m ‐2 . Microphytobenthic (MPB) contributions to the total (benthic + planktonic) chlorophyll a equated to 92, 89, and 84% at depths of 8, 16, and 20 m, respectively. Oxygen production in intact cores often exceeded consumption (e.g., by up to 2.5 mmol m‐2h ‐1 ) under near‐m situ conditions of light (8–30 μmol m ‐2 s ‐1 ). The feeding strategies of major components of the benthic macroinvertebrate fauna were used to identify possible pathways for utilisation of MPB production. MPB communities of more exposed subtidal locations in Tasman Bay were generally less dense and comprised of different species dominated by Pleurosigma amara and/or Paralia marina . We conclude that microalgal communities inhabiting the soft sediments in these regions can provide an important contribution to the benthic food web.

PACAP-38 is a chemorepellent and an agonist for the lysozyme receptor in Tetrahymena thermophila - S. R. Mace; J. G. Dean; J. R. Murphy; J. L. Rhodes; H. G. Kuruvilla (Journal of Comparative Physiology A, 2000)

Relative Distribution of Polychlorinated Biphenyls Among Tissues of Neonatal American Alligators ( Alligator mississippiensis ) - T. A. Bargar; C. Sills-McMurry; R. L. Dickerson; W. E. Rhodes; G. P. Cobb (Archives of Environmental Contamination and Toxicology, 1999)

Characterization of distinct Gal : 3-O-sulfotransferase activities in human tumor epithelial cell lines and of calf lymph node GlcNAc : 6-O-sulfotransferase activity - E. V. Chandrasekaran; Rakesh K. Jain; John M. Rhodes; Ram Chawda; Conrad Piskorz; Khushi L. Matta (Glycoconjugate Journal, 1999)

Aerobic and anaerobic energy during a 2-km race simulation in female rowers - L. P. Pripstein; E. C. Rhodes; D. C. McKenzie; K. D. Coutts (European Journal of Applied Physiology, 1999)

Identification of potentially toxic Pseudo‐nitzschia (Bacillariophyceae) in New Zealand coastal waters, using lectins - Lesley L. Rhodes (New Zealand Journal of Marine and Freshwater Research, 1998)
Identification of species within the do‐moic acid‐producing diatom genus Pseudo‐nitzschia is vital for biotoxin monitoring and decisions regarding shellfish harvesting, particularly when blooms are occurring. Several Pseudo‐nitzschia species produce high concentrations of domoic acid per cell, whereas others are non‐toxic, but all have similar morphologies using standard brightfield light microscopy. FITC‐conjugated lectins discriminated between the New Zealand derived species tested in this study, except for P. delicatissima and P. pseudo‐delicatissima . These results differ from those reported for Pseudo‐nitzschia species isolated from Galician (Spanish) waters, which suggests variability in production of surface sugars by these diatoms depending on geographical origin and/or environmental conditions. Ribosomal RNA‐targeted oligo‐nucleotide probes, at present being field trialled in several countries including New Zealand and the United States, are therefore still the preferred method of Pseudo‐nitzschia species identification underpinning New Zealand's biotoxin risk assessment programmes.

Coolia monotis (Dinophyceae): A toxic epiphytic microalgal species found in New Zealand (Note) - Lesley L. Rhodes; Annabel E. Thomas (New Zealand Journal of Marine and Freshwater Research, 1997)
Coolia monotis Meunier (Dinophyceae) was isolated from drift seaweed collected from Ninety Mile Beach, Northland, New Zealand. It is a new record for New Zealand waters. The microalga was identified by scanning electron microscopy and cultured in a seawater‐based medium. Cultures grew preferentially at 25°C (subtropical temperatures), rather than at 20°C (temperate), and at salinities >28. Coolia monotis proved to be toxic to larvae of Artemia salina and Haliotis virginea .

WATER ALLOCATION IN A CHANGING CLIMATE: INSTITUTIONS AND ADAPTATION - KATHLEEN A. Miller; STEVEN L. Rhodes; LAWRENCE J. Macdonnell (Climatic Change, 1997)

Biochemical characterization of simian foamy virus type I - F. Cavalieri; A. Rhodes-Feuillette; A. B. Benzair; R. Emanol-Ravicovitch; J. Peries (Archives of Virology, 1981)

The introduction and establishment of parasites of citrus blackfly,Aleurocanthus woglumi in Florida [Hem.: Aleyrodidae] - W. G. Hart; A. Selhime; D. P. Harlan; S. J. Ingle; R. M. Sanchez; R. H. Rhode; C. A. Garcia; J. Caballero; R. L. Garcia (BioControl, 1978)

The use of trypsin-treated human group 0 erythrocytes in rubella hemagglutination-inhibition test - S. Iwakata; L. P. Morrissey; A. J. Rhodes; N. A. Labzoffsky (Archives of Virology, 1974)

A possible new enterovirus serotype isolated in ontario - F. A. Richter; A. J. Rhodes; L. W. Macpherson; N. A. Labzoffsky (Archives of Virology, 1971)